EFFECTS OF GENDER STEREOTYPING ON WOMEN’S SOCIAL DEVELOPMENT: A CASE OF URBANIZED TURKANA WOMEN IN ELDORET TOWN-KENYA - Odette, Nahayo; Gisore, Billiah; Ojore, Aloys (Machakos University, 2019)
This study investigated the effects of gender stereotyping on urbanized Turkana women’s social development in Eldoret, Kenya. It identified the cultural factors that influence their involvement in social development. It also examined the role of local leaders in addressing gender stereotyping, while suggesting strategies that would address it and improve urbanized Turkana women’s participation in social development. The study utilized the Convergent Parallel Research Design. Consciousness Raising and Radical Feminist theories guided the study. The sample size was 549 respondents. Questionnaires, interviews and focus group discussions were used to collect data. Findings revealed that gender stereotyping has a negative moderate relationship with women’s social development with “r” value of -0.337. Results also demonstrate that there is a negative weak relationship between cultural factors and women’s social development with “r” = -0.131, and statistically influence it since “p” = 0.015, less than 0.05. Similarly, findings indicate that there is a negative weak relationship between local leaders and women’s social development with “r” = -0.201, and that they have a statistical influence on women’s social development since “p” = 0.000 which was less than the ideal value. Based on these results, the researcher proposes an action plan as a way forward. One of the proposed activities is the sensitization of Eldoret local leaders and the community on effects of gender stereotyping, creation of support groups for women to helps them to work together and have their voices heard. The researcher believes that the findings in this study will contribute to the fight against gender stereotyping and have more inclusiveness.
Keywords: Gender stereotyping; Women’s social development; Urbanized Turkana women